FUNDAMENTE PSIHOPEDAGOGICE DE FORMARE A INTERESELOR COGNITIVE LA ELEVI - USM ADMIN (Moldova State University, 2008)
This research is devoted to one of the most actual problems of present pedagogy and psychology - the formation and development of epistemological interests of younger pupil in the conditions of passing to a new paradigm of educa- tional policy, determined by the Concept of educational development in the Republic of Moldova, the Law of Education, National curriculum. The feature of the real research is the leaning on definitely new methodological basis: pragmatic philosophy, the theory of curriculum, the theory of activities, and the theory of forming education. In the thesis are deve- loped the psycho - pedagogical basis of forming and development of the epistemological interests of younger pupil: the most adequate theory of the interests, with respect to the pedagogical research, is established, are also established the stages, factors and conditions of forming the epistemological interests of younger pupil. The method of orientation- stimulation, of stirring up the educational activity of the students, is developed and experimenting checked, with the purpose of more effective forming of epistemological interests. The most important components of the suggested method are: the content, the technology, the estimation and the procedures in the sphere of these components, directed to stir up the productive and creative activity and to achieve success - the main stimulus of the epistemological interest.